EFEKTIVITAS PENDEKATAN KONSTRUKTIVISME TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI SMP NEGERI 5 SIPIROK - Ali Muhajir Siregar (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
This study aims to describe the effectiveness of using constructivism approach on students’ mathematical problem solving ability at the seventh grade students of SMP Negeri 5 Sipirok. The research was conducted by using quasi experimental method (pretest post test one group design) with 41 students as the sample and they were taken by using total sampling technique. Test and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using constructivism approach was 2.40 (good category) and b) the average of students’ mathematical problem solving ability before using constructivism approach was 48.73 (fair category) and after using constructivism approach was 75.51 (good category). Furthermore, based on inferential statistic by using paired sample ttest and helping SPSS version 16, the result showed the significant value was less than 0.05 (0.000<0.05). It means, there is a significant effective of using constructivism approach on students’ mathematical problem solving ability at the seventh grade students of SMP Negeri 5 Sipirok.